Manfaat Bladder Training Pada Pasien dengan Douwer Catheter - Kusumaningrum, Dwi Asih; Effendy, Christantie; Pangastuti, Heny Suseani (School of Nursing Faculty of Medicine Universitas Gadjah Mada, 2007)
Please refer to the file